Nicotinic acetylcholine receptors mediate donepezil‐induced oligodendrocyte differentiation. (22nd September 2015) - Imamura, Osamu; Arai, Masaaki; Dateki, Minori; Ogata, Toru; Uchida, Ryuji; Tomoda, Hiroshi; Takishima, Kunio
Abstract: Oligodendrocytes are the myelin‐forming cells of the central nervous system (CNS). Failure of myelin development and oligodendrocyte loss results in serious human disorders, including multiple sclerosis. Here, we show that donepezil, an acetlycholinesterase inhibitor developed for the treatment of Alzheimer's disease, can stimulate oligodendrocyte differentiation and maturation of neural stem cell‐derived oligodendrocyte progenitor cells without affecting proliferation or cell viability. Transcripts for essential myelin‐associated genes, such as PLP, MAG, MBP, CNPase, and MOG, in addition to transcription factors that regulate oligodendrocyte differentiation and myelination, were rapidly increased after treatment with donepezil. Furthermore, luciferase assays confirmed that both MAG and MBP promoters display increased activity upon donepezil‐induced oligodendrocytes differentiation, suggesting that donepezil increases myelin gene expression mainly through enhanced transcription. We also found that the increase in the number of oligodendrocytes observed following donepezil treatment was significantly inhibited by the nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine, but not by the muscarinic acetylcholine receptor antagonist scopolamine. Moreover, donepezil‐induced myelin‐related gene expression was suppressed by mecamylamine at both the mRNA and protein level. These results suggest that donepezil stimulates oligodendrocyte differentiation and myelin‐related gene expression via nAChRs in neural stem cell‐derived oligodendrocyte progenitor cells. We show that donepezil, a drug for the treatment of Alzheimer disease, can stimulate oligodendrocyte differentiation and maturation of oligodendrocyte progenitor cells. Transcripts for essential myelin‐associated genes, such as PLP, MAG, MBP, CNPase and MOG in addition to transcripton factors that regulate oligodendrocyte differentiation and myelination were rapidly increased after treatment with donepezil. These effects were partly dependent on nicotinic acetylcholine receptor (nAChR). Abstract : We show that donepezil, a drug for the treatment of Alzheimer disease, can stimulate oligodendrocyte differentiation and maturation of oligodendrocyte progenitor cells. Transcripts for essential myelin‐associated genes, such as PLP, MAG, MBP, CNPase and MOG in addition to transcripton factors that regulate oligodendrocyte differentiation and myelination were rapidly increased after treatment with donepezil. These effects were partly dependent on nicotinic acetylcholine receptor (nAChR). Cover Image for this issue: doi: 10.1111/jnc.12920 .